Penerapan Model Pembelajaran Kooperatif Tipe Make and Match untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Matematika Materi Pecahan Kelas V di SD Negeri 24 Toboali - Armala Armala; Didi Kriswanto (TIRAI: Jurnal Program Studi Manajemen Pendidikan Islam, 2023)
This study aims to improve student learning outcomes by applying the make a match type cooperative learning model in the mathematics subject for class V fractions at SD Negeri 24 Toboali in the 2022/2023 academic year. This research is a type of classroom action research. The research subjects were fifth grade students at SD Negeri 24 Toboali, totaling 24 students consisting of 13 male students and 11 female students. The object of research is the mathematics learning outcomes of fifth grade students at SD Negeri 24 Toboali in the 2022/2023 academic year. Data collection techniques using observation, written tests, and documentation. The data analysis technique used is descriptive qualitative and quantitative descriptive analysis. This research was said to be successful if 80% of students achieved KKM, namely 68. The results showed that 1) The average score of students who completed the first cycle was 64.16 and in the second cycle it increased to 80.41. In cycle I, the percentage of students who passed was 58.33% and in cycle II it rose to 87.5%; and 2) Increased student activity and response during learning activities experienced positive changes. Thus, it can be concluded that the application of the make a match type of cooperative learning model can improve the results of learning mathematics in fraction material in class V SD Negeri 24 Toboali.